The Determinant of Child Labor in East Java - Shelvia Rizky Arifanda (Jurnal Ilmiah Mahasiswa FEB, 2013)
Problem of child labor is a serious problem arises in much country in the world, including Indonesia. In Indonesia there is a huge number of child labor that finally gives a bad effect to the child, especially to the child education. Previous studies stated that problem of child labor is caused by some factors. By using probit model, this study examines the determinant of child labor in East Java. East Java is chosen because East Java is the second largest number of population with the third biggest number of child labor in Indonesia. The result shows that some factors such as child age; child gender; location; school attendance; household gender; household age; household education; and household occupation influence the probability of child to work. Key Words: Child Labor, Employment, Indonesia